Exploration of chemical components and metabolite synthesis pathways in eight Ephedra species based on HS-GC-MS and UPLC-Q-TOF-MS - Guo, Bing; Yang, Lina; Li, Hengyang; An, Qi; Liu, Yongli; Cheng, Jie; Hou, Fangjie; Guo, Long; Zhang, Dan (Frontiers in Plant Science, 2024)
Objective: Ephedra, widely used in clinical practice as a medicinal herb, belongs to the genus Ephedra in the family Ephedraceae. However, the presence of numerous Ephedra varieties and variants requires differentiation for accurate identification. Methods: In this study, we employed headspace gas chromatography mass spectrometry (HS-GC-MS), ultra-high performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF-MS), and global natural products social molecular networking (GNPS) for chemical component identification. Chemometric analysis was used to analyze the differential components. Metabolic analysis and Kyoto encyclopedia of genes and genomes (KEGG) enrichment were utilized to explore the synthesis pathways of different components. Result: A total of 83 volatile and 79 non-volatile components were identified in Ephedra species. Differential analysis revealed that among the eight Ephedra stems, 18 volatile and 19 non-volatile differential compounds were discovered, whereas Ephedra roots exhibited 21 volatile and 17 non-volatile markers. Volatile compounds were enriched in four synthetic pathways, while non-volatile components were enriched in five pathways among the differentiated components. Conclusion: This study is the first to conduct a comparative analysis of chemical components in different Ephedra species and parts. It provides a foundational reference for authenticating Ephedra herbs, evaluating medicinal resources, and comparing quality in future studies.